2012
DOI: 10.1155/2012/409757
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Ritchie's Method for Parasites Diagnosing with Minimization of Chemical Products

Abstract: Latin America, Africa, and Asia present wide dissemination and high prevalence rates of waterborne parasitic diseases, which is a strong indicative of the fragility of public sanitation systems. In this context, parasitological analyses represent extremely relevant instruments. Several parasite diagnosis methods exist, among which Ritchie's method (1948) stands out. This method uses formaldehyde and ether, two reagents of toxicological importance that can cause damages to environmental and occupational health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
11
0
3
Order By: Relevance
“…Some authors demonstrated that less toxic reagents could be used in replacement of ether as a solvent to extract fat and debris, like ethyl acetate (11), acetone (12), or tween (13). A modified version of Ritchie’s method by Régis Anécimo (14) did even replace both formaldehyde and ether by a natural detergent, yet had similar qualitative and quantitative performances in parasite recovery. Some protocols resort to sodium hydroxide (NaOH) to perform the formol-ether concentration technique, but a comparative study conducted by Suwansaksri et al (15) found no statistically significant difference when comparing its detection rate with a normal saline preparation, allowing to avoid the use of NaOH for security reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors demonstrated that less toxic reagents could be used in replacement of ether as a solvent to extract fat and debris, like ethyl acetate (11), acetone (12), or tween (13). A modified version of Ritchie’s method by Régis Anécimo (14) did even replace both formaldehyde and ether by a natural detergent, yet had similar qualitative and quantitative performances in parasite recovery. Some protocols resort to sodium hydroxide (NaOH) to perform the formol-ether concentration technique, but a comparative study conducted by Suwansaksri et al (15) found no statistically significant difference when comparing its detection rate with a normal saline preparation, allowing to avoid the use of NaOH for security reasons.…”
Section: Discussionmentioning
confidence: 99%
“…For this, 0.5 g fresh stool sample was added in the sample collecting tube containing 2.5 ml of formalin and 1 ml of ethyl acetate and the sample was well mixed and then centrifuged. Finally, the supernatant was discarded, the sediment mixed and put on the microscope slide for examination (20).…”
Section: Ritchie's Methodsmentioning
confidence: 99%
“…After took stool samples for modified Harada Mori, stool samples added with formalin 10% and examine for Lugol stain [16] and FEC [17] at laboratory.…”
Section: Methodsmentioning
confidence: 99%